Restrictive and Non-restrictive Noun Postmodification in Newspaper Discourse - Baumgärtner, Dominik (Univerzita Pardubice, 2021)
The paper focuses on the use of both phrasal and clausal noun postmodifiers, primarily from the semantic point of view, in the discourse of both American and British broadsheet newspapers. In the first part of this thesis, the theoretical framework concerning noun phrases, postmodifiers and newspaper discourse is introduced. In the practical part, the corpus-based analysis of postmodifiers is carried out, while the attention is devoted to the overall distribution of postmodifiers, their structure, usage and discrepancies of their use within individual articles.
Omezovací a neomezovací typy postmodifikací u anglické jmenné fráze v diskurzu novinových zpráv
Keywords: jmenná fráze; postmodifikace; sémantika; vztažné věty; přístavky; noviny; noun phrase; postmodification; semantics; relative clauses; apposition; newspaper